2013
DOI: 10.1149/2.027401jes
|View full text |Cite
|
Sign up to set email alerts
|

HDCFC Performance as a Function of Anode Atmosphere (N2-CO2)

Abstract: The mechanism for the oxidation of solid carbon in a fuel cell made as a hybrid between a molten carbonate fuel cell and a solid oxide fuel cell, known as a hybrid direct carbon fuel cell (HDCFC), was investigated. Fuel cell performance was measured by electrochemical impedance spectroscopy (EIS) and using current-potential-power density curves (I-V-P) between 700 to 800 • C. The impacts of the gas species introduced at the cathode (air vs. pure O 2 ) and at the anode (pure N 2 , pure CO 2 , and mixed N 2 -CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…We have previously reported on the effects of variable % CO 2 in mixed N 2 eCO 2 environments on carbon black fueled HDCFC performance, both in full-cell [2] and half-cell [4] configurations. Previously reported half-cell tests showed that current measured at fixed overpotential increased, and Rp values decreased, as the % CO 2 was increased.…”
Section: Mixed N 2 Ecomentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported on the effects of variable % CO 2 in mixed N 2 eCO 2 environments on carbon black fueled HDCFC performance, both in full-cell [2] and half-cell [4] configurations. Previously reported half-cell tests showed that current measured at fixed overpotential increased, and Rp values decreased, as the % CO 2 was increased.…”
Section: Mixed N 2 Ecomentioning
confidence: 99%
“…Briefly, there appear to be two prevailing theories on the dominant electrochemical reaction occurring in molten carbon-carbonate slurry DCFCs (co-electrolyte, MCFC-type DCFCs and HDCFCs): the complete oxidation of carbon (4 electron process) [36] and CO oxidation (2 electron process) [31]. We have previously suggested that the CO oxidation process likely predominates at the anode of planar HDCFCs [2]. Although non-coincident OCP and DE ¼ 0 values seen in our half-cell experiments in mixed N 2 eCO 2 (Fig.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 3 more Smart Citations